SR proteins SRp20 and 9G8 contribute to efficient export of herpes simplex virus 1 mRNAs - Escudero-Paunetto, Laurimar (2010)
Herpes simplex virus 1 (HSV-1) mRNAs are exported to the cytoplasm through the export receptor TAP/NFX1. HSV-1 multifunctional protein ICP27 interacts with TAP/NXF1, binds viral RNAs, and is required for efficient viral RNA export. In ICP27 mutant infections, viral RNA export is reduced but not ablated, indicating that other export adaptors can aid in viral RNA export. Export adaptor protein Aly/REF is recruited to viral replication compartments, however, Aly/REF knockdown has little effect on viral RNA export. SR proteins SRp20 and 9G8 interact with TAP/NXF1 and mediate export of some cellular RNAs. We report that siRNA knockdown of SRp20 or 9G8 resulted in about a 10 fold decrease in virus yields and in nuclear accumulation of poly(A+) RNA. In infected cells depleted of SRp20, newly transcribed Bromouridine-labelled RNA also accumulated in the nucleus. We conclude that SRp20 and 9G8 contribute to HSV-1 RNA export.